A Novel Model for Predicting the Well Production in High-Sulfur-Content Gas Reservoirs. (3rd May 2021) - Zou, Chunmei; Wang, Xiaodong; Hu, Jinghong; Lv, Yang; Fang, Bo; Zhang, Yuan
Abstract : High-content H2 S gas reservoirs are important for natural gas extraction. However, the precipitation and deposition of elemental sulfur in high-sulfur-content gas reservoirs eventually lead to porosity and permeability damage, resulting in the low well productivity. Therefore, it is worth developing an accurate production prediction model considering sulfur deposition for fractured horizontal wells. In this study, based on the partition model and transient percolation theory, a novel numerical model considering the damage of sulfur deposition with pressure change on reservoir porosity and permeability was first developed to predict the production from fractured horizontal wells in high-sulfur-content gas reservoirs. Then, it was validated by actual field data from a high-sulfur-content gas reservoir. After that, the influence of sulfur deposition on the production of fractured horizontal wells was revealed through theoretical calculations, and the effects of hydraulic fracture parameters on production were analyzed. The results show that elemental sulfur gradually deposits in the reservoir pores as the reservoir pressure decreases and the production time increases, which eventually leads to permeability damage and reduces reservoir productivity; this negative impact gradually increases over time. It is also shown that the production of fractured horizontal wells increases with an increase in the half-length, fracture conductivity, and fracture number. Compared with the fracture half-length, the fracture conductivity and fracture number have a greater influence on the production of a single well. The model can handle the influence of nonlinear parameters caused by sulfur deposition, which allows accurate calculations and provides guidance for the development of fractured horizontal wells in gas reservoirs with high sulfur content.